Pengaruh Lingkungan Kerja, Beban Kerja, dan Komitmen Organisasional terhadap Kinerja Karyawan Mathis Retreat Ubud - Purnami, Gusti Nyoman Verga; Abiyoga Wulandari, Ni Luh Adisti; Atim Purwaningrat, Putu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Human resources are one of the main elements for carrying out a business, where human resources are the operational drivers of a business, whether on a large or small scale. Good employee performance can be achieved with an optimal working atmosphere, good workload, and good organizational commitment. The problem formulation and objectives raised for this research“are to find the impact of the work environment, workload, and organizational commitment on employee performance.” This research took place at Mathis Retreat Ubud, a company operating in the hospitality and tourism sector. Furthermore, the sample population was all 30 employees who worked at Mathis Retreat Ubud.“Data were analyzed using Multiple Linear Regression techniques, Coefficient of Determination, t Test and F Test. Referring to the research results, it was found that the work environment had a partially positive and significant impact on employee performance, workload had a partially positive and significant impact on employee performance, organizational commitment had an impact partially positive and significant on employee performance and simultaneously the work environment, workload and organizational commitment have a significant impact on employee performance.